(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Objective: A modification of Friedewalds formula was proposed to calculate LDL cholesterol in Bangladeshi population up to serum triglyceride concentration of 1000 mg/dL. The aim of this study was to validate the modification of Friedewalds formula in Bangladeshi population. Methods: Serum total cholesterol, triglyceride, high-density lipoprotein cholesterol and low-density lipoprotein cholesterol concentrations were measured in specimens obtained form 314 adult Bangladeshi subjects selected conveniently. LDL cholesterol concentrations were also calculated by modified Friedewalds formula and original Friedewalds formula. Results were expressed as mean ± SD and calculated LDL cholesterol was compared with measured LDL cholesterol by two-tailed paired t test and Pearsons correlation coefficient (r). Results: The mean ± SD of measured LDL cholesterol was 138.3 ± 54.58 mg/dL. LDL cholesterol calculated by modified Friedewalds formula and original Friedewalds formula were 135.9 ± 59.26 mg/dL (P>0.05) and 123.5 ± 65.75 mg/dL (P<0.001) respectively. Compared to measured LDL cholesterol, calculated LDL cholesterol were 2.47 mg/ dL and 17.20 mg/dL lower for modified formula and original formula respectively. The correlation coefficient (r) with measured LDL cholesterol was 0.8601 (P<0.0001) for LDL cholesterol calculated by the modified Friedewalds formula and 0.8565 (P<0.0001) for the LDL cholesterol calculated by the original Friedewalds formula. Conclusion: The study validates the modified Friedewalds formula to calculate LDL cholesterol in Bangladeshi population. DOI: http://dx.doi.org/10.3329/jbcps.v30i3.12463 J Bangladesh Coll Phys Surg 2012; 30: 141-144